(untitled) (The Role of Exact Sciences in the Era of Modern Development, 2023)
This article is devoted to the field of phraseology, a branch of lexicology, which mainly classifies phraseologisms in linguistics. Subject of phraseology and types of word groups are discussed. The opinions of linguists are analyzed. They are given general conclusions.